Assessing the Digital Media Incorporation in teaching science at the intermediate level on Diyala Governorate: Descriptive-Analytic Study in the light of E-Learning Standards.: Penilaian Penerapan Media Digital dalam Pengajaran Ilmu Pengetahuan di Tingkat Menengah di Provinsi Diyala: Studi Deskriptif-Analitis Berdasarkan Standar E-Learning. - Sura Abdullah Hassan (Academia Open, 2026)
General Background The rapid expansion of digital technologies in education, particularly following the COVID-19 pandemic, has increased the need for systematic evaluation of technology integration in school environments. Specific Background In science education, digital media such as multimedia presentations, simulations, and online learning platforms are increasingly recognized as important instructional resources aligned with international e-learning standards. Knowledge Gap Despite this development, limited empirical evidence exists regarding the actual level of digital media incorporation in intermediate-level science classrooms within specific regional educational contexts. Aims This study examines the level of digital media integration in science teaching in intermediate schools in Diyala Governorate, Iraq, using internationally recognized e-learning standards as an analytical framework. Results Using a descriptive-analytical survey design and a structured questionnaire administered to science teachers, the findings indicate a moderate-to-low level of digital media usage, with teachers primarily relying on basic tools such as presentation slides and instructional videos. Advanced digital applications, including simulations and interactive technologies, are less frequently used. Teachers also reported significant barriers, including unstable internet connectivity, electricity interruptions, limited institutional support, and insufficient professional development opportunities. Novelty The study provides an empirical assessment of digital media practices in science classrooms through the lens of global e-learning competency frameworks. Implications The findings highlight the need for improved digital infrastructure, institutional policy alignment, and sustained professional training programs to support the systematic adoption of digital learning practices in science education. Keywords: Digital Media Integration, Science Education, E Learning Standards, Technology Integration, Teacher Readiness Key Findings Highlights Teachers rely mainly on presentations and instructional videos rather than advanced digital applications. Structural barriers such as internet instability and electricity interruptions remain major constraints. Positive teacher attitudes toward digital practices persist despite limited technological implementation.